PROTAGONIST SURVIVOR IN TELEVISION DRAMA SCENE - Novi Andayani; Zulfahmi Yasir Yunan (JOURNAL OF SCIENTIFIC COMMUNICATION (JSC), 2020)
This research discusses about message meaning of breast cancer in Korean Drama called Jealousy Incarnate. The concept is taken because breast cancer in men is still considered taboo in the society. Author uses Charles Sanders Peirce’s Semiotic Theory to analyze the meaning of messages in the South Korean television drama Jealousy Incarnate. The method use for this research is qualitative method. Author took data from SBS television drama, that is Wednesday and Thursday slots titles Jealousy Incarnate which the authors took from sources of indoxxi.tube, textbooks, electronic articles and publications related to the television drama Jealousy Incarnate, breast cancer, and Charles Sanders Peirce’s Semiotic Theory. The results of the analysis of this study indicate that in the Korean television drama Jealousy Incarnate there are scenes that contain messages about the protagonist survivor breast cancer in men. The drama made people aware, especially men, to be more cautious against breast cancer.